If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-2=2(x+2)+2
We move all terms to the left:
6x-2-(2(x+2)+2)=0
We calculate terms in parentheses: -(2(x+2)+2), so:We get rid of parentheses
2(x+2)+2
We multiply parentheses
2x+4+2
We add all the numbers together, and all the variables
2x+6
Back to the equation:
-(2x+6)
6x-2x-6-2=0
We add all the numbers together, and all the variables
4x-8=0
We move all terms containing x to the left, all other terms to the right
4x=8
x=8/4
x=2
| 4(-2x-1)=-8x+4 | | x9=64 | | 6+y=58 | | 7x+10-3x-9=-11 | | 15x=-2x−13 | | 15h=-2h−13 | | 1.6m+60=1.35m+61 | | -g+20=-16+g | | p-23=152 | | 14n+13+6n=-7+19n | | 5x+12=4x+ | | 516=180x÷x | | 19.8x-1.64=20x | | 3+x=74 | | x^2-800x-4600=0 | | 40-7u=u | | 24+9n-9=7n+9 | | 2p+11=-3 | | x-((x*6)/100)=2444 | | 2=+y/3=-1 | | 40-2x=3x+5 | | p-23=-7p+10+5p | | 5x+3=4/3+x | | 16x-4-x=26 | | U+10=6u | | a^2−7a+12=0 | | -6x+10=-6x-12 | | -6+2n=3+4n+7 | | 24=8x-(2x+36) | | 2y+12=6y | | 5z^2+18z+9=0 | | -6+2n=3+4n |